2004
DOI: 10.1348/000712604322779451
|View full text |Cite
|
Sign up to set email alerts
|

Individual and group modelling of aesthetic judgment strategies

Abstract: Individual differences in aesthetic judgments were investigated by comparing quantitative group and individual performance models of the judgment processes. Aesthetic judgments of beauty over novel, formal, graphic patterns were collected from 34 non-artist college students using a two-step ranking-rating procedure. Their judgment processes were individually modelled using Judgment Analysis. The participants showed noted individual differences. Certain features of the stimulus material, which were considered t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
82
0

Year Published

2008
2008
2024
2024

Publication Types

Select...
6
3

Relationship

2
7

Authors

Journals

citations
Cited by 87 publications
(87 citation statements)
references
References 21 publications
5
82
0
Order By: Relevance
“…These were considered to be perceptual cues that could be used by the participants in deriving their judgments. Accordingly the features were employed in the judgment analysis (i.e., they were introduced as predictors in the multiple regression analysis; Jacobsen, 2004). See the Appendix for the intercorrelation matrix of all 20 features.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…These were considered to be perceptual cues that could be used by the participants in deriving their judgments. Accordingly the features were employed in the judgment analysis (i.e., they were introduced as predictors in the multiple regression analysis; Jacobsen, 2004). See the Appendix for the intercorrelation matrix of all 20 features.…”
Section: Methodsmentioning
confidence: 99%
“…Also, it was predicted that group models and individual case models replicate previous reports of symmetry and complexity as determinants of aesthetic judgments. In addition, on the basis of reports of individual differences in aesthetic judgment (e.g., Fechner, 1876;Jacobsen, 2002Jacobsen, , 2004Whitfield, 1984) individual judgmental variation was predicted.…”
Section: The Present Studymentioning
confidence: 99%
“…These theories often relied on psychophysical studies aiming to identify particular stimulus properties that induce aesthetic experience. Studies of the so-called 'golden section' in abstract geometrical figures provide one example (McManus & Weatherby, 1997), but similar approaches have been used with paintings (Jacobsen & Hofel 2002;Jacobsen, 2004;Jacobsen, Buchta, Kohler & Schroger, 2004;Whissell, 1980;McManus, 1980). Such studies generally suggest that aesthetic experience depends on compositional arrangement between parts of the stimulus, and between individual parts and the whole.…”
Section: Introductionmentioning
confidence: 99%
“…For example, Jacobsen (2004) modeled IDs in the preference for simple spatial compositions and isolated specific cues that seemed to drive the preference decisions in different individuals. McManus (1980) showed that preference for the shapes of triangles and rectangles varies widely across individuals and yet is consistent within an individual over a time span of more than 2 years.…”
mentioning
confidence: 99%